Hyphenated Techniques as Tools for Plant Growth/Development Monitoring and Plant Product Quality Assessment - Tarkowski, Petr (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
Among all analytical techniques used for the analysis of biomolecules, hyphenated techniques such as LC-MS, GC-MS, CE-MS are the major platforms for chemical profiling, metabolomics, and quality control. The brief overview of above mentioned techniques utilized in the quantification of several different classes of low-molecular-weight substances, from phytohormones, which are present in minute concentrations in plant tissue, to amino acids, polyamines, cannabinoids, terpenoids, phenolics, fatty acids, and vitamins that are important bioactive compounds in some plant-based products, is presented here. The advantages and drawbacks of each particular method are discussed, from sample preparation to data processing. In addition, the significance of proper chemical analyses of plant genetic resources in combination with genotyping and phenotyping will be discussed.